Foundations of public economics - Starrett, David A. (Cambridge economic handbooks, 1988)
Discusses the major theoretical foundations of modern public sector economics. Includes market failures encompassing externalities, pure public goods, local public goods and natural monopolies. Representative voting, benefit cost analysis, incentive compatible design mechanisms and the free market are points also covered. Special attention is paid to financial arrangements, techniques for eliciting necessary information and identification of biases that will result from incorrect procedures.